Antiphospholipid syndrome, antiphospholipid antibodies, and stroke. Issue 4 (April 2023) - Mittal, Prabal; Quattrocchi, Graziella; Tohidi-Esfahani, Ibrahim; Sayar, Zara; Chandratheva, Arvind; Cohen, Hannah
Antiphospholipid syndrome (APS) is a prothrombotic autoimmune disease with heterogeneous clinicopathological manifestations and is a well-established cause of acute ischemic stroke (AIS) and transient ischemic attack (TIA), particularly in younger patients. There is growing recognition of a wider spectrum of APS-associated cerebrovascular lesions, including white matter hyperintensities, cortical atrophy, and infarcts, which may have clinically important neurocognitive sequalae. Diagnosis of APS-associated AIS/TIA requires expert review of clinical and laboratory information. Management poses challenges, given the potential for substantial morbidity and recurrent thrombosis, additional risk conferred by conventional cardiovascular risk factors, and limited evidence base regarding optimal antithrombotic therapy for secondary prevention. In this review, we summarize key features of APS-associated cerebrovascular disorders, with focus on clinical and laboratory aspects of diagnostic evaluation. The current status of prognostic markers is considered. We review the evidence base for antithrombotic treatment in APS-associated stroke and discuss uncertainties, including the optimal intensity of anticoagulation and efficacy of direct oral anticoagulants. Clinical practice recommendations are provided, covering antithrombotic treatment, supportive management, and options for anticoagulant-refractory cases, and we highlight the benefits of adopting a considered, multidisciplinary team approach.